Analisis Daya Saing Ekspor Udang Beku Indonesia di Jepang dan Faktor-Faktor yang Memengaruhinya Tahun 1989-2019 - Amalia Restu Damayanti; Sugiarto Sugiarto (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2022)
Frozen shrimp is Indonesia's leading fishery export. In the world, Indonesia is ranked fourth as the largest frozen shrimp exporter. One of Indonesia's target markets is Japan. However, among other countries, only Indonesian frozen shrimp has a downward trend. If this decline continues, it could make Indonesia lose its frozen shrimp export market, that is Japan. The purpose of this study was to describe the competitiveness of Indonesian frozen shrimp in Japan and determine the factors that influence it in the long and short term. The analytical methods used is Error Correction Mechanism. The results showed that Indonesian frozen shrimp had good competitiveness with fluctuations and increasing trends. Factors that affect competitiveness in the long and short term are exchange rates, export volumes, world shrimp prices, and export values of competing countries. Indonesia's GDP percapita only has an effect in the long term, while the IJEPA policy has no effect.